A revision of the genus Protomicroplitis Ashmead (Hymenoptera, Braconidae, Microgastrinae), with the description of a new species - Fernandez-Triana, J.l. (Zootaxa, 2015)
The New World genus Protomicroplitis is revised. One new species is described from Central America, a dichotomous key and extensive illustrations for the three known species are provided. The genus has a restricted distribution, from Canada (45° N) to Costa Rica (10° N). Two species of Condica (Lepidoptera: Noctuidae) are the only known hosts. The following new taxonomic and nomenclatural acts are made. New species: Protomicroplitis centroamericanus Fernandez-Triana. New combinations: Diolcogaster alce (Nixon, 1965), Diolcogaster breviterebrus Rao & Chalikwar, 1970, Diolcogaster coenonymphae (Watanabe, 1937), Diolcogaster erro (Nixon, 1965), Diolcogaster glaphyra (de Saeger, 1944), Diolcogaster integra (Wilkinson, 1929), Diolcogaster medon (Nixon, 1965), Diolcogaster melleus (Nixon, 1965), Diolcogaster nephele (Nixon, 1965), Diolcogaster orientalis (Rao & Chalikwar, 1970), Diolcogaster pyrene (Nixon, 1965), Diolcogaster rugulosus (Rao & Chalikwar, 1970), Diolcogaster urios (Nixon, 1965). Revised combinations: Choeras tegularis (Szépligeti, 1905), Diolcogaster seriphus (Nixon, 1965).